Persistent Idiopathic Dentoalveolar Pain : literature review and clinical case treated with intraoral application of Botulinum toxin = Dolor Idiopático Dentoalveolar Persistente (DIDAP) : revisión de literatura y caso clínico tratado con aplicación intraoral de toxina Botulínica - Cervantes Chavarría, Andrés R 1986-
Persistent Idiopathic Dentoalveolar Pain (PIDAP) is an orofacial neuropathic pain, which can be difficult to diagnose and is usually accompanied by increasing anxiety from both the patient and the treating dentist. A case of a 38-year-old female patient is presented, and it is shown the diagnostic process and therapeutic approach. The interdisciplinary management accompanied by several pharmacological lines is highlighted: Botulinum toxin was used as an adjunctive treatment allowing it to decrease systemically administered medications dosing and therefore its possible side effects. This condition usually affects psychosocial aspects of the patient and has a major impact on his quality of life. It is very important before initiating an invasive clinical treatment, obtaining a clear differential diagnosis and assessing in some cases the presence of non-odontogenic pain, such as PIDAP.